2019
DOI: 10.1371/journal.pone.0214272
|View full text |Cite
|
Sign up to set email alerts
|

Research misconduct in health and life sciences research: A systematic review of retracted literature from Brazilian institutions

Abstract: Background Measures to ensure research integrity have been widely discussed due to the social, economic and scientific impact of research integrity. In the past few years, financial support for health research in emerging countries has steadily increased, resulting in a growing number of scientific publications. These achievements, however, have been accompanied by a rise in retracted publications followed by concerns about the quality and reliability of such publications. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 26 publications
1
44
0
3
Order By: Relevance
“…Of the three major forms of research misconduct (Office of Science and Technology Policy, 2000), plagiarism (79 instances) was much more prevalent than fabrication or falsification, with only 12 instances recorded. In fact, it appears that problems with publication ethics—notably plagiarism, as well as duplication of articles (70 instances) and authorship issues (22 instances)—can be regarded as an issue that warrants more attention on the African continent as well as globally (Damineni et al, 2015; Grieneisen and Zhang, 2012; Stavale et al, 2019; Wager and Williams, 2011). Plagiarism has been identified as an issue that tends to be more prevalent in low- and middle-income countries where lack of training and awareness, combined with limited resources, cultural factors, and language barriers have been listed as possible reasons (Ana et al, 2013; Hesselmann et al, 2017; Rohwer et al, 2017; Stretton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three major forms of research misconduct (Office of Science and Technology Policy, 2000), plagiarism (79 instances) was much more prevalent than fabrication or falsification, with only 12 instances recorded. In fact, it appears that problems with publication ethics—notably plagiarism, as well as duplication of articles (70 instances) and authorship issues (22 instances)—can be regarded as an issue that warrants more attention on the African continent as well as globally (Damineni et al, 2015; Grieneisen and Zhang, 2012; Stavale et al, 2019; Wager and Williams, 2011). Plagiarism has been identified as an issue that tends to be more prevalent in low- and middle-income countries where lack of training and awareness, combined with limited resources, cultural factors, and language barriers have been listed as possible reasons (Ana et al, 2013; Hesselmann et al, 2017; Rohwer et al, 2017; Stretton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Authors such as Schmidt (2018) indicated that there is scope for improvement in formulation of journal policies on retraction and a need to use standard terminology in the formulation of retraction notices. Others such as Hosseini et al (2018) and Stavale et al (2019) urged for a clearer distinction between retractions that are due to good science citizenship, such as corrections or revisions, and retractions that are due to misconduct or questionable research practices.…”
Section: Best Practicesmentioning
confidence: 99%
“…[4] Insufficient analysis reduces its validity and the readers may not show any interest in the aforementioned implications of the study. [5] In this study,[1] the results look spurious and extremely theoretical, with no practical validity. The authors should have used appropriate tests to make conclusions from their data because various errors have been overlooked, which reduces the utility of this study.…”
mentioning
confidence: 90%
“…Public retraction associated with publications may be due to misconduct, gross errors or fraud, with plagiarism being the main factor. 5 From a writing point of view, plagiarism can be considered substantially copying and pasting, making a literal copy of a text, paraphrasing (placing words in the middle of copied text), or recycling a text (self-plagiarism). 6 We can also divide plagiarism into four main forms: 7 • Form: it represents the copy of sentences or sentences taken from another text; • Content: uses previous data, without the given express authorization of the author, such as definitions, figures, and images;…”
Section: Plagiarism In Scientific Publicationsmentioning
confidence: 99%